Classical Japanese Literature in the Global Context (on Genji monogatari) - Andassova M.М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
The main problem of studying classical Japanese literature from a global perspective is, of course, related to translation. This article uses the original text of the Genji Monogatari 源氏物語 (The Tale of Genji) and its translations into English and Russian to examine the specific construction of a sentence in old Japanese, which does not specify the subject, as well as words and expressions that have no analogues in European languages. The article also discusses the peculiarities of the methodology of literature research due to the difference in the scientific approach of the Japanese and European scientific worlds